Discoid lupus erythematosus in an adolescent aged 16. - Pisani, V. (European Journal of Pediatric Dermatology, 2010)
A 16-year-old subject was first observed due to asymptomatic, reddish facial lesions persisting from 5 months. The family history revealed thyroiditis and multiple sclerosis in two maternal aunts. The lesions started on the nose and then others appeared on the face and scalp. Physical examination showed lesions rounded or elongated, erythematous, hyperkeratotic on the nose, forehead, cheeks, lower lip and scalp, where there was rarefaction of hair (Fig. 1, 2). A histological examination showed perifollicular lymphocytic infiltrate with follicular hyperkeratosis and vacuolar degeneration of cells of the basal layer (Fig. 3). Laboratory tests were within normal limits except for the presence of antinuclear antibodies in low titre (1/320). The final diagnosis was discoid lupus erythematosus.